Da infância do mágico à gênese do lobo: a mitologia de Harry Haller em O Lobo da Estepe, de Hermann Hesse - Schenkel , Klara Maria (2018)
This research investigates the repertoire of the "personal mythology" of Harry Haller, the protagonist of the novel Steppenwolf (Der Steppnwolf, 1927), by Hermann Hesse. In addition to the eclectic "mosaic of quotations" selected by Harry Haller to narrate his inner conflicts, Hesse's autobiographical data are deliberately interspersed with literary creation. In this sense, by crossing the boundaries between life and work (or between "real" and "fictional"), Hesse’s "autofiction" seeks provocative dialogue with a multifaceted otherness, through which Haller / Hesse attempts to achieve his "unity ". For this, the strictly subjective point of view will not suffice: the protagonist will have to occupy the territory of the Other and decentralize himself, he will have to be subject and object, to overcome the "fiction of the ego", and finally, he will have to overcome the dualistic view and then recognize a less provisional truth about himself and what he calls his "personal mythology". Removed from the aseptic and ordered world of the bourgeoisie and from the romantic promise of rediscovering the lost paradise, the mythos of this lone wolf goes through important issues in vogue in the period that succeeded the First Great War in the Germanic soil. The vast trajectory of Harry Haller's mythology - from the works of Goethe and Novalis to Nietzsche's tragic thought, from the German counterculture to Jung's Analytic Psychology and to Indian "gnosis" - reveals above all the genesis of a "multipersonalistic subject” that foreshadows the collapse of bourgeois values and of Modernity itself, a subject that would require new literary forms of expression.